Catecholamine excretion profiles identify clinical subgroups of neuroblastoma patients. (April 2019) - Verly, I.R.N.; Leen, R.; Meinsma, J.R.; Hooijer, G.K.J.; Savci-Heijink, C.D.; van Nes, J.; Broekmans, M.; Wanders, R.J.A.; van Kuilenburg, A.B.P.; Tytgat, G.A.M.
Abstract: Introduction: Analysis of urinary catecholamine metabolites is one of the primary modalities to diagnose patients with neuroblastoma. Although catecholamine excretion patterns have been recognised in the past, their biological rationale and clinical relevance remain largely unknown. Therefore, this study was designed to identify unique catecholamine excretion patterns and elucidate their underlying biology and clinical relevance. Patients and methods: A panel of 25 neuroblastoma cell lines was screened for catecholamine excretion. Detection of the catecholamine enzymes was performed using Western blot. Based on catecholamine enzymes presence and excreted catecholamine metabolites, excretion profiles were defined. The prevalence of these profiles was investigated in vivo using diagnostic urines from 301 patients with neuroblastoma and immunohistochemistry on primary tumours. The clinical relevance of the profiles was determined by linking the profiles to clinical characteristics and outcome of patients with neuroblastoma. Results: Four excretion profiles (A-D) were identified in vitro, which correlated with the relative protein expression of the catecholamine enzymes. These profiles were also identified in urine samples from patients with neuroblastoma and correlated with the presence of the catecholamine enzymes in the tumour. Strikingly, in 66% of the patients, homovanillic acid and vanillylmandelic acid excretions were discordant with the catecholamine profiles. Clinical characteristics and outcome gradually improved from patients with profile A (predominantly high risk) towards profile D (predominantly observation), with 5-years overall survival of 35% and 93%, respectively. Conclusions: Catecholamine profiles in vitro and in vivo reflect, to a large extent, the presence of the individual catecholamine enzymes and represent distinct subgroups of patients with neuroblastoma. Highlights: Catecholamine profiles reflect relative expression of the catecholamine enzymes. Homovanillic acid and vanillylmandelic acid excretion is discordant with the catecholamine profiles. Each profile represents a unique clinical subgroup of patients with neuroblastoma. Clinical characteristics and outcome gradually improved from profile A towards D. Catecholamine non-excreting patients (profile D) have excellent outcome.